Alkali Metal Cations as Charge‐Transfer Bridge for Polarization Promoted Solar‐to‐H2 Conversion. (19th December 2022) - Wang, Meiyang; Zhang, Zhenzong; Chi, Zexu; Lou, Lan‐lan; Li, Hui; Yu, Han; Ma, Tianyi; Yu, Kai; Wang, Hao
Abstract: Utilization of spontaneous polarization electric field of ferroelectric materials to realize the spatial separation and fast transfer of photogenerated charges has been regarded as a promising strategy to fabricate highly efficient photocatalysts. Herein, a novel heterostructure is constructed by coupling potassium poly(heptazine imide) (K‐PHI) with ferroelectric Bax Sr1‐x TiO3 (Bx ST) through a facile electrostatic self‐assembly strategy. The ionic species of K‐PHI can neutralize the polarized charges in Bx ST to form intimate interfacial contact, substantially boosting the internal electric field. Notably, K + cations intercalated into K‐PHI act as charge‐transfer bridge to promote migration and separation of photogenerated charge carriers. As a result, a significantly improved H2 ‐evolution rate of 1087.4 µmol h −1  g −1 with an apparent quantum yield (AQY) of 8.05% at 420 nm is achieved over 5% K‐PHI/B0.8 ST, standing among the best polymeric carbon nitride‐based photocatalysts reported up to date. Moreover, the extreme stability of the catalysts is evidenced by remaining outstanding catalytic performance even after storage for half a year. This strategy can be extended to other alkali metal (Na + and Cs + ) modified polymeric materials, highlighting the key role of the bridging ions in constructing polarized heterostructure, which sheds light on the design of ferroelectric‐assisted photocatalysts. Abstract : Alkali metal cations intercalated into polymeric carbon nitride acts as charge‐transfer bridge to fabricate polarization promoted heterostructure with boosting spatial separation efficiency of charge carriers and superior solar‐to‐H2 performance, highlighting the crucial role of the bridging ions in constructing ferroelectric‐assisted photocatalysts.